Determination of cisplatin in human blood plasma and urine using liquid chromatography-mass spectrometry for oncological patients with a variety of fatty tissue mass for prediction of toxicity - Gerina-Berzina, A.; Hasnere, S.; Kolesovs, A.; Umbrashko, S.; Muceniece, R.; Nakurte, I. (Experimental Oncology, 2017)
Aim: The research was aimed to analyze a level of triglycerides in blood serum as a possible new marker of toxicity, particularly in patients with excess body weight, receiving cisplatin. Materials and Methods: Study involved 20 oncological patients with stage III lung cancer, who received palliative treatment with cisplatin. High-performance liquid chromatography was used for quantitative determination of pure cisplatin in urine and blood samples. Cisplatin concentration of the test samples was determined based on the data obtained from the calibration graph. Results: Quantitative determination of pure cisplatin is quite complicated. The elimination half-time for one of the groups was observed higher almost by half than for other patients. Higher dose of cisplatin showed a significant association with increase in triglyceride levels. We found a close correlation between body mass index and triglyceride changes during chemotherapy (p = 0.001; r = 0.67). The results indicate that a higher body mass index gives higher fluctuations of triglyceride levels in blood serum. Analyses of correlation between level of triglycerides and elimination half-time show that by an increase in the level of triglycerides in the blood serum cisplatin elimination half-time is prolonged (R²Linear = 0.596). Cisplatin concentration in urine is higher and elimination takes longer time at elevated levels of triglycerides, where close correlation between fraction of excreted substance in urine and concentration parameters was seen (p < 0.01). Also good correlation for body mass index with fraction of excreted substance in urine and concentration parameters was observed (p < 0.05). Conclusion: Clearance of cisplatin, which was determined by the chromatographic method, is reduced in individuals with increased adipose tissue mass. Research data suggest that overweight affects cisplatin elimination from the body. The greater body fat mass can contribute to a greater rise of triglyceride level in blood serum. Triglycerides in blood plasma may serve as an additional indicator of higher cisplatin toxicity as a cardiotoxicity marker.